Pengaruh Hypnoteraphy Terhadap Nyeri Pada Ibu Post Sectio Caesarea DI RS PMC - Suheimi, Kardimatus; Sari, Endah Purwani; Winda, Desy (JURNAL PENDIDIKAN KESEHATAN, 2024)
Sectio Caesarea is a way to deliver a baby if there are pathological indications for vaginal delivery. The incision causes moderate to severe pain. One way to reduce post-cesarean section pain is Hypnotherapy. Hypnotherapy is superior to other therapies, namely it only uses the power of suggestion and thoughts which change brain waves into alpha and theta conditions so that it immediately relaxes the patient and the patient becomes more comfortable in a fairly short time. Research Objectives: This research aims to determine the effect of Hypnotherapy on pain levels in mothers. post caesarean section. Method: This research is a Quasi Experimental Design research with a pre test and post test nonequivalent control group design. The research sample was post caesarean section mothers consisting of 12 people in the intervention group who were given a combination of analgesics and hypnotherapy and 12 people in the control group who were only given analgesics and taken using purposive sampling. The research instrument was a pre-test and post-test sheet on a numerical scale (Numerical Rating Scale or NRS). Results: The results of the Marginal Homogeneity test showed that there was a significant decrease in pain levels before and after treatment in the intervention group, namely p=0.001 (p 1 (p<0.005) while in the control group there was a decrease in pain levels but it was not significant before and after treatment, namely p= 0.007. The results of the Chi Square test in the 2 groups showed a value of p=0.000 (p which means there was a difference in the level of pain in the intervention group which was given a combination of analgesics and hypnotherapy and the control group which was only given analgesics. Conclusion: The combination of analgesics and hypnotherapy had a greater effect on reducing levels post caesarean section pain compared to just analgesics as a sole therapy. Hypnotherapy is recommended for nurses and patients. Trained nurses can develop Hypnotherapy skills as a complementary therapy to deal with patient pain and patients can also be taught to do self-hypnosis as an alternative for dealing with pain.